(untitled) (Al-Qamar, 2025)
The rapid integration of Artificial Intelligence (AI) into educational systems worldwide has prompted critical ethical, cultural, and religious evaluations of its use, particularly in the context of Islamic education. This study explores the Islamic ethical guidelines related to the use of AI in teaching and learning, with specific reference to preserving traditional teacher-student relationships, intellectual integrity, and the spiritual objectives of education in Islam. The research investigates how AI tools, while offering pedagogical efficiency and access to information, may also inadvertently lead to dependency, reduced critical thinking, and violations of privacy and authenticity. The study further examines the implications of AI usage on academic honesty, the risk of disseminating inaccurate or non-authentic religious content, and the potential weakening of human-centered educational values. Drawing from Quranic principles, Prophetic traditions, and classical Islamic scholarship, the research identifies key ethical parameters for the responsible integration of AI in education. By analyzing these dimensions, the paper aims to develop a framework that aligns modern technological advancements with the moral and epistemological foundations of Islamic teachings. This inquiry contributes to the broader discourse on the compatibility of emerging technologies with faith-based educational models, offering practical guidelines for educators, institutions, and policymakers operating within Islamic contexts.